2008
DOI: 10.1007/s10933-008-9213-7
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variability of Holocene climate: a palaeolimnological study on varved sediments in Lake Jues (Harz Mountains, Germany)

Abstract: Studies combining sedimentological and biological evidence to reconstruct Holocene climate beyond the major changes, and especially seasonality, are rare in Europe, and are nearly completely absent in Germany. The present study tries to reconstruct changes of seasonality from evidence of annual algal successions within the framework of well-established pollen zonation and 14 C-AMS dates from terrestrial plants. Laminated Holocene sediments in Lake Jues (10°20.7 0 E, 51°39.3 0 N, 241 m a.s.l.), located at the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 75 publications
3
37
0
4
Order By: Relevance
“…was a general trend in the whole of Europe. It was recorded in the Netherlands (Van Geel et al 1996), Switzerland (Holzhauser et al 2005), Northern Ireland (Swindles et al 2007), Finland ), Germany (Voigt et al 2008) and Sweden (Andersson and Schoning 2010). It corresponds to a widespread climate reversal identified at the Sub-boreal to Sub-atlantic transition (Van Geel et al 1996).…”
Section: Postglacial History Of Vegetationmentioning
confidence: 93%
“…was a general trend in the whole of Europe. It was recorded in the Netherlands (Van Geel et al 1996), Switzerland (Holzhauser et al 2005), Northern Ireland (Swindles et al 2007), Finland ), Germany (Voigt et al 2008) and Sweden (Andersson and Schoning 2010). It corresponds to a widespread climate reversal identified at the Sub-boreal to Sub-atlantic transition (Van Geel et al 1996).…”
Section: Postglacial History Of Vegetationmentioning
confidence: 93%
“…In varved sediments it is possible to assess yearly flux rates of pollen, to define rates of palaeoenvironmental changes and to describe them on decadal and even subdecadal scales (Birks and Birks 2006). Holocene palaeoecological reconstructions including pollen studies from varved sediments were obtained for several European areas, for instance in Scandinavia (Anderson et al 1996;Haltia-Hovi 2010;Ojala et al 2008), Germany (Kerig and Lechterbeck 2004;Kubitz 2000;Leroy et al 2000;Litt et al 2001;Voigt et al 2008), Switzerland (e.g. Haas et al 1998;Lotter 1999;Tinner et al 2003) and France (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This species was also found in a lagoon (Colombia) (Montoya- Moreno et al, 2013) and in Animas river (USA), where heavy metals loading is present (Sgro, Poole, & Johansen, 2007). Otherwise, it is a fossil species found in some sediment core samples (Voigt, Grüger, Baier, & Meischner, 2008;Loakes, 2015). We found this species at H003 station of Lake Hazar in Elazığ (Turkey).…”
Section: Resultsmentioning
confidence: 57%
“…Also, this species was recorded as a new taxon for Bulgarian algal flora in a study in Boyanska River (Isheva & Ivanov, 2014). Otherwise, in some studies it was found in sediment cores (Voigt et al, 2008;Loakes, 2015). Ludwig and Schnittler (1996) reported that this taxon is also in red list category (endangered species) for Germany.…”
Section: Resultsmentioning
confidence: 96%